Three new species of Craterispermum (Rubiaceae) from Madagascar - de Block, Petra; Randriamboavonjy, Tianjanahary (Phytotaxa, 2015)
The Afro-Madagascan genus Craterispermum (Craterispermeae, Rubiaceae) is taxonomically badly known. Hitherto, no species were described from Madagascar, although several taxa occur in the humid lowland forests in the eastern and northern regions of the island. In this contribution three new Madagascan Craterispermum species are described, C. motleyanum, C. puffianum and C. cervicorne. All are illustrated and their distribution is discussed. An identification key for the three new species is given.